P109 Routine hepatitis C antibody testing in MSM – are we overtesting?. (8th June 2017) - Robinson, Michael; Jeffery, Katie; Edwards, Anne
Abstract : Introduction: The hepatitis C virus (HCV) is rarely transmitted sexually. MSM with HIV are at increased transmission risk. Debate exists regarding sexual transmissibility of HCV in those without HIV or additional risk factors beyond receptive anal intercourse. Following outbreaks of HCV in Europe and London in MSM, Oxfordshire Sexual Health Services introduced annual unselected HCV antibody testing as a screening minimum for all MSM. Evidence now suggests this may not be necessary. We set out to audit our HCV testing to assess this and identify potential policy modification. Methods: We reviewed all HCV antibody tests undertaken in a 12 month period. We identified all HCV positive patients to determine risk factors for infection in order to establish whether these patients were identified through annual screening or would have been identified using a selective basic risk analysis. Results: We found 13 positive results out of 1351 tests. 6 had previously known HCV, 4 were co-infected with HIV. 2 were heterosexual men with additional risk factors, one was an MSM with additional risk factors. No HIV negative MSM with HCV infection were identified through annual screening alone. Approximately 3.5% of tests undertaken were based on recognised risk factors for HCV, 96.5% were undertaken as part of annual screening. This equated to £1486 per new diagnosis, excluding service costs. Discussion: Routine annual screening of HIV negative MSM in this study did not pick up any new HCV diagnoses. Cost per diagnosis may be reduced with targeted testing. The annual screening policy needs modification.